2013
DOI: 10.1007/s00436-013-3491-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the adjuvant effect of pidotimod on the immune protection induced by UV-attenuated Toxoplasma gondii in mouse models

Abstract: The current anti-Toxoplasma gondii drugs have many shortcomings and effective vaccines against T. gondii may contribute to the control of this pathogen. Pidotimod is a synthetic substance capable of stimulating both cellular and humoral immunity. To investigate the possible adjuvant effect of pidotimod on the immune response to T. gondii in Kunming mice induced by ultraviolet-attenuated T. gondii (UV-T.g), in this study, mice were immunized intraperitoneal (i.p.) with UV-T.g or UV-T.g co-administered with pido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
2
7
0
1
Order By: Relevance
“…Our data are largely consistent with prior studies that utilized UV inactivation of T. gondii tachyzoites (Endo, et al, 1981, Grimwood, 1980, Lu, et al, 1999, Yang, et al, 2010, Zhao, et al, 2013). For example, we also showed that tachyzoites exposed to UV were able to exclude Trypan blue, suggesting irradiation did not damage the tachyzoite membrane (Grimwood, 1980).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our data are largely consistent with prior studies that utilized UV inactivation of T. gondii tachyzoites (Endo, et al, 1981, Grimwood, 1980, Lu, et al, 1999, Yang, et al, 2010, Zhao, et al, 2013). For example, we also showed that tachyzoites exposed to UV were able to exclude Trypan blue, suggesting irradiation did not damage the tachyzoite membrane (Grimwood, 1980).…”
Section: Discussionsupporting
confidence: 91%
“…We found that 1 minute UV-exposed tachyzoites did not replicate in vitro, as has been seen by others using UV inactivation of tachyzoites (Endo, et al, 1981, Grimwood, 1980). In addition, we report that mice administered inactivated parasites had a robust serological IgG response without a decrease in body weight, as has been previously published (Yang, et al, 2010, Zhao, et al, 2013). …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…It is capable of stimulating humoral and cellular immunity 2 , activate natural killer cell, enhance the phagocytic function of macrophage and neutrophilic granulocyte, promote the proliferation of lymphocyte induced by mitogens, and increase the production of cytokines such as Interleukin 2 and γ-interferon 3,4,5 .…”
Section: Introductionmentioning
confidence: 99%